Surface analysis and biocompatibility of titanium alloy after wire electro-discharge machining (WEDM) / Nornisaadila Musa - Musa, Nornisaadila (2020)
The high demand of Ti-6Al-4V in medical industries becoming a concern nowadays. Titanium is a suitable material for orthopedic implants, dentistry and cardiovascular aids due to high resistance, immunity to corrosion, high fracture strength, osseointegration, low modulus and density. As the titanium is one of the most expensive materials and is categorised as a difficult-to-machine material, it is governed by the limitation of being machined through conventional machining. Hence, the problem in machining titanium can be solved by an alternative non-conventional machining process. A wire electro-discharge machining (WEDM) is able to machine the electrically conductive materials and with no physical contact between the workpiece and wire electrode which aids in keeping the material non-toxic for medical applications. The toxicity of the material has to be tested by way of biocompatibility testing. This research aims to develop the machining WEDM surface roughness prediction model through Artificial Neural Network (ANN), to characterise the machined surface of Ti-6Al-4V through WEDM and to determine the influences of machining processes on the biocompatibility of the machined part. The preliminary WEDM cutting operation helps in identifying the parameters and levels for the actual